Childhood adversity and clinical and psychosocial outcomes in psychosis. (2020) - Turner, S.; Harvey, C.; Hayes, L.; Castle, D.; Galletly, C.; Sweeney, S.; Shah, S.; Keogh, L.; Spittal, M. J.
Abstract: Aims: Associations between childhood abuse and various psychotic illnesses in adulthood are commonly reported. We aim to examine associations between several reported childhood adverse events (sexual abuse, physical abuse, emotional abuse, neglect and interpersonal loss) among adults with diagnosed psychotic disorders and clinical and psychosocial outcomes. Methods: Within a large epidemiological study, the 2010 Australian National Survey of Psychosis (Survey of High Impact Psychosis, SHIP), we used logistic regression to model childhood adverse events (any and specific types) on 18 clinical and psychosocial outcomes. Results: Eighty percent of SHIP participants (1466/1825) reported experiencing adverse events in childhood (sexual abuse, other types of abuse and interpersonal loss). Participants reporting any form of childhood adversity had higher odds for 12/18 outcomes we examined. Significant associations were observed with all psychosocial outcomes (social dysfunction, victimisation, offending and homelessness within the previous 12 months, and definite psychosocial stressor within 12 months of illness onset), with the strongest association for homelessness (odds ratio (OR) = 2.82). Common across all adverse event types was an association with lifetime depression, anxiety and a definite psychosocial stressor within 12 months of illness onset. When adverse event types were non-hierarchically coded, sexual abuse was associated with 11/18 outcomes, other types of abuse 13/18 and, interpersonal loss occurring in the absence of other forms of abuse was associated with fewer of the clinical and psychosocial outcomes, 4/18. When adverse events types were coded hierarchically (to isolate the effect of interpersonal loss in the absence of abuse), interpersonal loss was associated with lower odds of self-reproach (OR = 0.70), negative syndrome (OR = 0.75) and victimisation (OR = 0.82). Conclusions: Adverse childhood experiences among people with psychosis are common, as are subsequent psychosocial stressors. Mental health professionals should routinely enquire about all types of adversities in this group and provide effective service responses. Childhood abuse, including sexual abuse, may contribute to subsequent adversity, poor psychosocial functioning and complex needs among people with psychosis. Longitudinal research to better understand these relationships is needed, as are studies which evaluate the effectiveness of preventative interventions in high-risk groups.